Between Boredom and Frustration: Predictor of Compulsive Internet Use - Rahayu Hardianti Utami; Elrisfa Magistarina; Mario Pratama; Andhita Nurul Khasanah (Jurnal Neo Konseling, 2021)
Internet users have various purposes or motives for using internet service. Furthermore, internet usage proliferated by 40 percent amidst the COVID-19 pandemic social confinements. Interestingly, there is a tendency to do activities with the internet when under load or overload circumstance. This study aims to look at these two contradictory conditions and determine whether when someone is in a state of the tendency to be bored or depressed due to stressful conditions becomes a predictor for using the internet maladaptively. This study uses a quantitative approach with an accidental sampling technique. We recruited 235 internet users from adolescents to middle adulthood. The result showed boredom proneness and frustration intolerance predicted 34.4% of internet users' compulsive internet use. This study also showed a more significant impact of boredom to compulsive internet use rather than frustration intolerance. These findings indicate that people tend to use the internet more frequently in under load than overload conditions.